Neonatal Meckel diverticulum: Obstruction due to a short mesodiverticular band. Issue 5 (26th August 2015) - Kunitsu, Tomoaki; Koshida, Shigeki; Tanaka, Katsunori; Nakahara, Sayuri; Yanagi, Takahide; Maruo, Yoshihiro; Takeuchi, Yoshihiro; Kubota, Yoshihiro
Abstract: This is the first report of symptomatic Meckel diverticulum in a newborn, in which direct compression by a short mesodiverticular band (MDB) caused intestinal obstruction. A short MDB can cause intestinal obstruction due to direct compression. There are two mechanisms by which Meckel diverticulum with MDB can cause intestinal obstruction: internal hernia and direct compression. Onset of intestinal obstruction due to direct compression by a short MDB might be earlier than that for internal hernia with long MDB.